Pendidikan Dan Pelestarian Kearifan Lokal: Studi Komparatif Tradisi Kampung Adat Cireundeu - Fatmawati, Fitri; Nurjanah, Nurul; Juniati, Asti; Septianingsih; Maulana, Ana (CV. Kurnia Grup, 2024)
The purpose of this study is to investigate how education in the Cireundeu Traditional Village contributes to the preservation of local knowledge, particularly with regard to understanding cultural values ​​and customs that have passed down through the generations. The Cireundeu Traditional Village case study employs a qualitative methodology that includes in-depth interviews with community members, educators, and traditional authorities. The study's findings show that formal and informal education are integrated in Cireundeu, where traditional and cultural values ​​are taught through everyday activities and formal education in schools. Furthermore, this study discovered that the Cireundeu community's customs are successfully maintained and preserved using this local wisdom-based strategy. According to the study's findings, the government should support the incorporation of local wisdom into Indonesia's formal education system since it can serve as a template for cultural preservation in other areas.